How to achieve safe, high-quality clinical studies with non-Medicinal Investigational Products? A practical guideline by using intra-bronchial carbon nanoparticles as case study. Issue 1 (December 2016) - Berger, M.; Kooyman, P.; Makkee, M.; van der Zee, J.; Sterk, P.; van Dijk, J.; Kemper, E.
Abstract Background Clinical studies investigating medicinal products need to comply with laws concerning good clinical practice (GCP) and good manufacturing practice (GMP) to guarantee the quality and safety of the product, to protect the health of the participating individual and to assure proper performance of the study. However, there are no specific regulations or guidelines for non-Medicinal Investigational Products (non-MIPs) such as allergens, enriched food supplements, and air pollution components. As a consequence, investigators will avoid clinical research and prefer preclinical models or in vitro testing for e.g. toxicology studies. The aim of this article is to 1) briefly review the current guidelines and regulations for Investigational Medicinal Products; 2) present a standardised approach to ensure the quality and safety of non-MIPs in human in vivo research; and 3) discuss some lessons we have learned. Methods and results We propose a practical line of approach to compose a clarifying product dossier (PD), comprising the description of the production process, the analysis of the raw and final product, toxicological studies, and a thorough risk-benefit-analysis. This is illustrated by an example from a human in vivo research model to study exposure to air pollutants, by challenging volunteers with a suspension of carbon nanoparticles (the component of ink cartridges for laser printers). Conclusion With this novel risk-based approach, the members of competent authorities are provided with standardised information on the quality of the product in relation to the safety of the participants, and the scientific goal of the study.